2021
DOI: 10.1007/s00170-021-07517-1
|View full text |Cite
|
Sign up to set email alerts
|

Joining thin-walled structures without protuberance by two-strokes flattening clinching process

Abstract: Clinching technologies have better performance in joining different sheet materials. However, the protuberance and mechanical behaviors of clinched joints have always been needed to be improved. In this paper, a new clinching method, named two-strokes attening clinching (TFC) process, was proposed to improve the mechanical behaviors of joints and atten the protuberance. Mechanical testing including tension shearing tests were employed under quasi-static conditions to evaluate the different mechanical behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They found that the shear strength and tensile strength were higher when the neck fracture occurred. Peng et al [15] conducted shear mechanical tests, cross-sectional profile measurements and failure mode analysis on two-stroke flat clinched (TFC) joints and clinched joints of Al1060 aluminum sheets. It was found that the neck thickness, interlock value, and shear strength of TFC joints are higher than those of clinched joints, and the failure modes are neck fractures.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the shear strength and tensile strength were higher when the neck fracture occurred. Peng et al [15] conducted shear mechanical tests, cross-sectional profile measurements and failure mode analysis on two-stroke flat clinched (TFC) joints and clinched joints of Al1060 aluminum sheets. It was found that the neck thickness, interlock value, and shear strength of TFC joints are higher than those of clinched joints, and the failure modes are neck fractures.…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded that the joint was subjected to tensile stress. Peng et al 11,12 proposed a reshaping method to decrease the bulge height of clinched joint. A flat die was utilized to compress the joint from die side and neck thickness of joint increased, resulting in larger strength of joint.…”
mentioning
confidence: 99%